Differences in size and architecture of the potato cultivars root system and their tolerance to drought stress - Krystyna ZARZYŃSKA; Dominika BOGUSZEWSKA-MAŃKOWSKA; Artur NOSALEWICZ (Plant, Soil and Environment, 2017)
Drought can cause substantial yield losses, particularly for crops with shallow root systems, such as potato (Solanum tuberosum). This study tested whether root system architecture could affect potato yield under drought conditions. The following parameters of the roots were measured: depth range, total length, total area, surface area, average diameter, and total dry weight of the root system. These parameters in soil layers were also measured at different depths. Five potato cultivars from a group of mid-early cultivars were examined in this study. The same cultivars were tested under two conditions: control with optimal irrigation and drought stress treatment without irrigation for three weeks after the end of tuberization to check the tuber yield. Significant differences were observed among cultivars in the size of the root system and its architecture. The biggest differences in the individual layers of soil profile related to the diameter of the root, the root length, and the surface area. Also a relationship between the size of the root system and yield of tubers was found. The strongest correlations involved the root length and the root surface area with the decrease in tuber yield under the drought, then the dry root mass with the decrease in yield. These correlations were negative: the higher the value of the parameter, the smaller the observed decrease in yield. This showed a relationship between root length and mass with the decrease of yield; this relationship was stronger for roots in deeper layers than in the shallowest layers. Therefore, this study indicates that breeding potato cultivars with deep root systems might improve tuber yields under drought conditions.